1981
DOI: 10.23986/afsci.72064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liming on the magnesium status of some mineral soils and on the fate of fertilizer magnesium

Abstract: Nine mineral soils were incubated in laboratory without lime (Ca0) or limed (Ca1) with calcium carbonate (lab.reag.), and without magnesium fertilizer (Mg0) or fertilized with MgSO4*7H20 (Mg1 = 4 mg/100 g soil Mg). The incubation covered a period of seven weeks in aerobic conditions at constant 20 °C temperature. The relative increase in the effective cation exchange capacity (ECEC) caused by liming seemed to be in coarse mineral soils greater than in clay soils. The differences in pH (CaCl2) values between so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…In this pot experiment the dolomitic limestones seemed to have a smaller effect on the effective CEC than the same amount of calcitic limestone. It has also been reported that the effective CEC of soil is not affected by either magnesium sulphate (GROVE et al 1981, JOKINEN 1981 or magnesium carbonate (GROVE et al 1981) (HUNSAKER andPRATT 1970, McBRIDE 1978) or other reactions due to the high aluminium content of the soil (KINNIBURG et al 1976, CHAN et al 1979, GROVE et al 1981 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this pot experiment the dolomitic limestones seemed to have a smaller effect on the effective CEC than the same amount of calcitic limestone. It has also been reported that the effective CEC of soil is not affected by either magnesium sulphate (GROVE et al 1981, JOKINEN 1981 or magnesium carbonate (GROVE et al 1981) (HUNSAKER andPRATT 1970, McBRIDE 1978) or other reactions due to the high aluminium content of the soil (KINNIBURG et al 1976, CHAN et al 1979, GROVE et al 1981 …”
Section: Resultsmentioning
confidence: 99%
“…If the pH of soil containing only small amounts of plant available magnesium is raised by the application of calcitic limestone, the need for the addition of magnesium becomes even greater because some of the soil magnesium is converted in a form not extractable in neutral ammonium acetate (McLEAN 1956, ADAMS and HENDERSON 1962, KAILA 1974, GROVE et al 1981, JOKINEN 1981. Similarly, some of the readily-soluble magnesium applied to the soil is converted into the not extractable form OUO andUZU 1977, JOKINEN 1981 (KAILA 1971) The growing season 1979 was extremely wet.…”
Section: Introductionmentioning
confidence: 99%
“…In the second growing season with N addition and K shortage, timothy seemed to be stronger than clover in the competition on K, and therefore the K content of clover remained lower than without N. The earlier results of field studies also imply the existence of competition on K between clover and timothy (Raininko 1968, Jokinen 1969).…”
Section: Discussionmentioning
confidence: 95%
“…The possible reason for the decreased growth may be e.g. the high Ca concentration in the soil (Munns and Fox 1976), the inbalance in Ca/Mg (Jokinen 1981 a), the incapacity to take up non-exchangeable cations (unlike ryegrass) and decrease in nodule number, nodule weight and N fixation (Edwards et al 1981, Ssali 1981. Edwards et al (1981) obtained the highest yield increases of cowpea with 2.5 t/ha lime at pH 4.3; higher lime amounts decreased the yield.…”
Section: Discussionmentioning
confidence: 99%
“…Bunun nedeni bölgedeki sıcak ve kurak iklim koşullarının yanında, bölgedeki düşük yağış nedeniyle, yıkanmanın olmamasıdır. Ayrıca, bitki besin elementlerinin dengesi bakımından ideal bir tarım toprağında Ca/Mg= 6, Ca/K= 12, Mg/K= 2 olması beklenmektedir (Jokinen 1981). Bölge topraklarının Ca/Mg oranlarının %11.6'sı, Ca/K oranlarının %14.3'ü ve Mg/K oranlarının %37'si bu oranlara uymaktadır.…”
unclassified